2005
DOI: 10.1097/00008390-200502000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma of unknown primary: experience at Massachusetts General Hospital and Dana-Farber Cancer Institute

Abstract: Melanoma may present metastatically without an identifiable primary lesion. To further characterize the epidemiology of melanoma of unknown primary (MUP), we report our experience with a cohort of MUP patients. We retrospectively reviewed patients seen at the Massachusetts General Hospital (MGH) and the Dana-Farber Cancer Institute (DFCI) between 1986 and 1996 with follow-up to 2002. Data were analysed using log-rank and proportional hazards analyses, with death from any cause as the main outcome measure. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 0 publications
4
98
1
5
Order By: Relevance
“…9 3,7,13 However, some 6,10 seem to indicate higher survivals for MUP patients compared to reported survivals from larger stage IV studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…9 3,7,13 However, some 6,10 seem to indicate higher survivals for MUP patients compared to reported survivals from larger stage IV studies.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies report a guarded prognosis, 9,12 while others demonstrate a more favorable survival for stage IV disease from MUP versus melanoma from a known primary (MKP; Table 1). 4,6 We previously reported a favorable outcome after regional lymphadenectomy for clinical stage III melanoma from MUP versus MKP. 15 We hypothesized that if this survival advantage reflects an immunologic response to melanoma, then it should apply to patients with distant metastasis from MUP.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma cases with unknown primary origin are rarely seen, constituting 2-6% of all malignant melanoma cases (3)(4)(5). In the study conducted by de Waal et al (4), the primary origin was reported to be unknown in 857 (2.6%) of 33,181 melanoma patients monitored between 2003 and 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Prevención secundaria (46,47,48,49,50,51) Las fotografías secuenciales son básicas para el seguimiento de nevos sospechosos en los individuos con gran número de nevos y nevos displaśicos.…”
Section: Prevención Primaria Y Autocuidado De La Pielunclassified